A new titanium alloy with a combination of high strength, high strain hardening and improved ductility. (1st January 2015) - Sun, F.; Zhang, J.Y.; Marteleur, M.; Brozek, C.; Rauch, E.F.; Veron, M.; Vermaut, P.; Jacques, P.J.; Prima, F.
Abstract : A ternary β-metastable titanium Ti–9Mo–6W (wt.%) was designed. A very high work hardening rate close to 2100 MPa and a uniform deformation larger than 35% were recorded, thanks to combined transformation-induced plasticity and twinning-induced plasticity effects. In this paper, detailed microstructural analysis was performed to understand the deformation process. Various mechanisms, 3 3 2〈1 1 3〉 mechanical twinning, stress-induced ω phase and stress-induced α″ martensite were identified after mechanical testing, resulting in a complex network of deformed microstructures with very special synergetic features.